ENGLISH AND UZBEK NATIONAL DANCE TERMINOLOGY (European Journal of Interdisciplinary Research and Development, 2024)
This article explores the history and cultural significance of dance in both England and Uzbekistan. English Morris Dancing: It delves into the origins of Morris dancing, a traditional English folk dance accompanied by music and rhythmic stepping. It highlights the dance's transformation from a courtly activity to a popular folk dance and its revival in the early 20th century. The article focuses on Khoresm dance, a specific style rich in arm and leg movements, with variations for both men and women. It mentions prominent dances like "Lazgi" and its different versions, along with the traditional clothing worn by performers.